Comprehensive analysis of MQTT 5.0 susceptibility to network covert channels. Issue 104 (May 2021) - Mileva, Aleksandra; Velinov, Aleksandar; Hartmann, Laura; Wendzel, Steffen; Mazurczyk, Wojciech
Abstract: Message Queuing Telemetry Transport (MQTT) is a publish-subscribe protocol which is currently popular in Internet of Things (IoT) applications. Recently its 5.0 version has been introduced and ensuring that it is capable of providing services in a secure manner is of great importance. It must be noted that holistic security analysis should also evaluate protocol's susceptibility to network covert channels. That is why in this paper we present a systematic overview of potential data hiding techniques that can be applied to MQTT 5.0. We are especially focusing on network covert channels that, in order to exchange secrets, exploit characteristic features of this MQTT version. Finally, we develop proof-of-concept implementations of the chosen data hiding techniques and conduct their performance evaluation in order to assess their feasibility in practical setups.